Geometric Distortion Correction of Renal Diffusion Tensor Imaging Using the Reversed Gradient Method. Issue 2 (March 2021) - Lim, Ruth P.; Lim, Jeremy C.; Teruel, Jose R.; Botterill, Elissa; Seah, Jas-mine; Farquharson, Shawna; Ekinci, Elif I.; Sigmund, Eric E.
Abstract : Abstract: Renal echo planar diffusion tensor imaging (DTI) has clinical potential but suffers from geometric distortion. We evaluated feasibility of reversed gradient distortion correction in 10 diabetic patients and 6 volunteers. Renal area, apparent diffusion coefficient, fractional anisotropy, and tensor eigenvalues were measured on uncorrected and distortion-corrected DTI. Corrected DTI correlated better than uncorrected DTI ( r = 0.904 vs 0.840, P = 0.002) with reference anatomic T2-weighted imaging, with no significant difference in DTI metrics.